1992
DOI: 10.1207/s15327051hci0703_2
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Indirect Collaborative Design With Integrated Knowledge-Based Design Environments

Abstract: We are developing a conceptual framework and a demonstration system for collaboration among members of design teams when direct communication among these members is impossible or impractical. Our research focuses on the long-term, indirect communication needs of project teams rather than the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…At the level of an individual artifact (e.g., a particular computer network evolving over many years), we have emphasized the need for long-term, indirect collaboration [Fischer et al, 1992], which takes place when an artifact functions and is repeatedly redesigned over a relatively long period of time. Fischer Collaboration and communication between designers is not only asynchronous with respect to time and place, but it is indirect in the sense that groups of designers may have no opportunity to meet or communicate directly.…”
Section: Collaboration and Communication Between Stakeholders As Facimentioning
confidence: 99%
“…At the level of an individual artifact (e.g., a particular computer network evolving over many years), we have emphasized the need for long-term, indirect collaboration [Fischer et al, 1992], which takes place when an artifact functions and is repeatedly redesigned over a relatively long period of time. Fischer Collaboration and communication between designers is not only asynchronous with respect to time and place, but it is indirect in the sense that groups of designers may have no opportunity to meet or communicate directly.…”
Section: Collaboration and Communication Between Stakeholders As Facimentioning
confidence: 99%
“…In addition to supporting individual designers to design, DODEs support long-term indirect collaboration between designers [5]. Long-term collaboration is required in the design of complex and evolving artifacts, which are maintained and modified over a span of years.…”
Section: Two Levels Of Contextmentioning
confidence: 99%
“…Experiments [39] showed that users often invoked the critic too late, after a ACM Transactions on Information Systems, VoL 19 …”
Section: Framer-extending Construction Kits To Design Environments Fmentioning
confidence: 99%
“…These changing environments require design environments that designers can adapt to fit unanticipated needs. Initial domain knowledge in our design environments is represented in seeds [19]. The seeds consist of objects in the palette, examples in a catalog, critics and argumentation.…”
Section: Modifier-making Critics User-extensiblementioning
confidence: 99%
See 1 more Smart Citation